Condições de saúde, estilo de vida e risco de ulceração nos pés de pessoas com diabetes mellitus atendidas na atenção primária - Rossaneis, Mariana Angela (2015)
Ulceration on the feet is one of the disorders with higher economic and social impact for the person with diabetes mellitus (DM) due to the high mutilation potential. The study had the objective of analyzing health conditions, lifestyle and the ulceration risk in the feet of people with type II diabetes mellitus who have been attended in the primary healthcare service. It is a cross-sectional study carried out in a large city in the south of Brazil. The stratified sampling per region of the municipality comprised 1,515 subjects. The participants were selected by drawing lot among diabetic patients registered in the 38 Primary Healthcare Services. The data collection was done by utilizing an instrument consisting of demographic variables, lifestyle, clinical conditions, self-care with the feet and clinical examination of the lower limbs. The glycemic control was determined by laboratory exam of glycosylated hemoglobin (HbAc1) and considered normal when it presented a result lower than 7%. The clinical examination of the feet assessed dermatologic, orthopedic and vascular aspects in order to determine the risk of developing ulcers. The bivariate statistical analysis was done with simple and hierarchical Poisson regression analysis in order to identify the factors associated to the risk of feet ulcers. Findings identified that the sampling consisted, mainly, of elderly, white people, low education level, economic class C and subjects who lived with a partner. There was a predominance of subjects with hypertension blood pressure and overweight. Men presented higher prevalence of self-care deficits due to low frequency of drying the interdigital spaces, no periodical assessment of the feet, habit of walking barefoot, lack of feet hygiene and inadequate cutting of nails. They also showed higher deficit prevalence in the self-referred food control and no performance of laboratory exams regarding the lipid profile. However, they presented lower prevalence in the practice of hot footbath and in wearing inadequate footwear when compared to women. The HbAc1 alteration was present in 68.9% of the participants with higher prevalence among subjects of age between 50 and 69 years and those who depend on insulin and have high body mass index and undergo risk of feet ulceration. The risk of feet ulceration was prevalent among men, subjects aged over 70 years and those who did not practice a regular physical activity and with diagnosis time over 10 years besides among insulin dependent patients and those with retinopathy and history of cerebrovascular accident. Mycosis on the nails and in the interdigital spaces was associated to higher prevalence of feet ulceration risk after the adjustment of all levels in the hierarchic model. Findings show that DM lack of control and the related chronic disorders are prevalent and difficult to prevent with aging and higher diagnosis time of the disease. Therefore people with such characteristics should undergo a rigorous follow-up by the family health care team. The nurse, who manages the care in the primary health care service, must develop intervention strategies that consider risk factors besides the social, economic and cultural context of the subjects in order to avoid or to delay emerging DM chronic disorders.